Social Repercussion of Translocating a Jaguar in Brazil - Martins, Cláudia S. G.; Engel, Mônica T.; Guimarães, Maria Augusta; Paolino, Roberta M.; Schulz, Francine; Esteves, Carolina Franco (Frontiers in Conservation Science, 2022)
The translocation of ‘problem-animals’ is a common non-lethal strategy to deal with human-wildlife conflict. Processes of wildlife translocation have been widely documented, but little is known about the social repercussions that take place once the capture and the return of a problem-animal to its natural habitat fail and it has to be permanently placed in captivity. We investigated how the public perceived the translocation of a jaguar to a wildlife captivity center. The objectives were to assess the public's perceptions towards the jaguar and its translocation process, and find out how these psychological constructs are related. We used the social media profiles of the three institutions involved in the process and analysed the comments left by their followers on posts related to the jaguar and the translocation itself. A total of 289 comments were analysed through coding, a categorizing strategy of qualitative analysis; 33 codes were identified. Results showed high admiration for the work done, positive attitudes and emotions, and concern toward the animal. Lack of awareness about the translocation process was high, with comments of curiosity toward the situation being one of the most commonly found. To a lesser extent, people felt sad for the jaguar not being able to return to the wild and criticized the need for translocation. Admiration for the work had a strong relation with gratitude and broader positive perceptions toward the jaguar’s story. Criticism related to concern, which was also related to a need for more information and curiosity. Findings suggest that the public who engaged with those institutions through their Instagram accounts were grateful for seeing the jaguar safe, but were not aware of the complexity of the operation nor about the nature of the conflict with farmers. The public can either reinforce a particular action or jeopardize an entire operation. We acknowledge the limitations of our sample and recommend further analyses of social repercussions among people who are not followers of these organizations; and, engaging other stakeholders to fully understand the human dimensions of translocating this jaguar. Finally, we highlight the importance of transparency and reliability of the organizations operating the translocation.